Pemikiran Pendidikan Humanistik dalam Islam - Musthofa Musthofa (Hikmah: Journal of Islamic Studies, 2017)
Since its birth, Islam has brought a humanitarian mission as it is manifested in the apostolate of Muhammad with the main vision of mercy and kindness to humankind. Islamic education is built on the humanitarian mission with a goal to humanize humans (humanization). In other words, Islamic education is very close to human values. The thought about education that humanizes humans brings to the concept of humanistic education. The concept of humanistic education is strongly influenced by three philosophical thoughts namely pragmatism, progressivism, and existentialism. Each of them contributes a lot to the thoughts of humanistic education. Humanistic is interpreted more asone approach of education that uses humanism approach. This paper explores the process of humanizing humans (humanization) in the concept of humanistic education as an issue and the main goalsince the birth ofIslam. The process of humanizing people in Islamic education is manifested in the process of humanization, liberation, and transcendence which have strong roots in the teachings ofIslam.